5.7k views
3 votes
Y" - 4y = (x2 - 3) sin 2x

1 Answer

5 votes

y''-4y=0

has characteristic equation


r^2-4=0

which has roots at
r=\pm2, giving the characteristic solution


y_c=C_1e^(2x)+C_2e^(-2x)

For the nonhomogeneous part of the ODE, let
y_p=(a_2x^2+a_1x+a_0)\sin2x+(b_2x^2+b_1x+b_0)\cos2x. Then


{y_p}''=(-4b_2x^2+(8a_2-b_1)x+4a_1-4b_0+2b_2)\cos2x+(-4a_2x^2+(-4a_1-8b_2)x-4a_0+2a_2-4b_1)\sin2x

Substituting into the ODE gives


(-8b_2x^2+(8a_2-b_1)x+4a_1-8b_0+2b_2)\cos2x+(-8a_2x^2+(-8a_1-8b_2)x-8a_0+2a_2-4b_1)\sin2x=(x^2-3)\sin2x

It follows that


\begin{cases}-8b_2=0\\8a_2-8b_1=0\\4a_1-8b_0+2b_2=0\\-8a_2=1\\-8a_1-8b_2=0\\-8a_0+2a_2-4b_1=-3\end{cases}\implies\begin{cases}a_2=-\frac18\\\\a_1=0\\\\a_0=(13)/(32)\\\\b_2=0\\\\b_1=-\frac18\\\\b_0=0\end{cases}

which yields the particular solution


y_p=-\frac18x^2\sin2x+(13)/(32)\sin2x-\frac18x\cos2x

So the general solution is


y=y_c+y_p

y=C_1e^(2x)+C_2e^(-2x)-\frac18x^2\sin2x+(13)/(32)\sin2x-\frac18x\cos2x
User Chris Arthur
by
6.1k points